The influence of hypertensive disorders of pregnancy on the development of long-term postpartum type 2 diabetes mellitus - Shota Inoue; Yasunori Takata; Yasuharu Tabara; Koutatsu Maruyama; Ayaka Yoshida; Haruhiko Osawa; Takashi Sugiyama (Endocrine Journal)
The association between hypertensive disorders of pregnancy (HDP) and the subsequent development of type 2 diabetes (T2D) in Japanese general population remains unclear. To investigate the influence of HDP on long-term postpartum development of metabolic disorders and T2D, we conducted a population-based cross-sectional study using the 75 g oral glucose tolerance test (75g-OGTT) in 978 parous Japanese women (median age: 66 years). We further evaluated the combined effect of HDP and T2D susceptibility genes on developing T2D. HDP history was identified in 101 participants (10.3%) and associated with high blood pressure, hypertriglyceridemia, increased homeostasis model assessment 2 for insulin resistance, decreased Matsuda index and insulin secretion-sensitivity index-2, increased postprandial glucose levels during the 75g-OGTT, and increased prevalence of hypertension, metabolic syndrome and T2D. The age and BMI adjusted odds ratio (OR) for T2D was 1.74 (95%CI: 1.04–2.93) in individuals with HDP as compared to those without HDP. Stratified analyses demonstrated an increased OR of T2D prevalence for individuals with HDP history harboring the cyclin-dependent kinase 5 regulatory subunit associated protein 1-like 1 (CDKAL1) C/C genotype compared with that of the reference group after adjusting for age and current BMI (OR = 5.18 vs. reference group; 95% CI: 1.99–13.50). Further, validation analyses using bootstrap method showed high reproducibility. HDP history was associated with postpartum prevalence of hypertension, insulin resistance and T2D later in life in Japanese general population. Further, the simultaneous assessment of an HDP history and CDKAL1 genotype is valuable to predict the future T2D development (UMIN000036074).